AB0311 Clinical Responses and Synovial Vascularity in Obese Rheumatoid Arthritis Patients Treated with Adalimumab and Methotrexate. (15th July 2016) - Kaeley, G.S.; Ranganath, V.K.; MacCarter, D.K.; Pangan, A.L.; Wang, X.; Kalabic, J.
Abstract : Background: Obese rheumatoid arthritis (RA) patients (pts) may have higher levels of inflammatory mediators, greater joint swelling and tenderness, and suboptimal response to therapy. Objectives: We assessed disease activity and treatment response in obese RA pts, using ultrasonography (US) and clinical measures. Methods: This post hoc analysis used observed data from the MUSICA trial 1 which evaluated the efficacy of high [20 mg/week (wk)] or low (7.5 mg/wk) doses of methotrexate (MTX) in combination with adalimumab (ADA) for 24 weeks (wks) in RA pts with previous inadequate response to MTX who initiated ADA. Pts were grouped according to body mass index (BMI) at baseline (BL): normal BMI <25; overweight BMI ≥25-<30; obese BMI ≥30. Synovial vascularity and hypertrophy were measured by Power Doppler US and Greyscale respectively, bilaterally, at metacarpophalangeal (MCP) joints 2, 3, 5, metatarsophalangeal joint 5 (MTP5) and wrists. Swollen joint count (SJC) of 66 joints, tender joint count (TJC) of 68 joints, 28-joint count Disease Activity Score using C-reactive protein (DAS28-CRP), and numbers of pts reaching American College of Rheumatology (ACR) criteria, Clinical Disease Activity Index [CDAI] low disease activity (LDA, <10), DAS28-CRP low disease activity (LDA; DAS<3.2), were assessed at wks 12 and 24. Results: Out of 308 pts at BL, 69 pts (22.4%) had BMI <25, 102 pts (33.1%) had BMI ≥25-<30 and 137 pts (44.5%) had BMI ≥30. Disease characteristics and ultrasound disease assessments were similar for the 3 BMI subgroups at BL. At wks 12 and 24, compared with pts in the normal and overweight categories, obese pts tended to have numerically smaller mean changes from BL in SJC66, TJC68, DAS28-CRP, synovial hypertrophy and synovial vascularity (table ). Compared to pts in the normal and overweight categories, significantly fewer obese pts reached ACR20/50 at wks 12 and 24. Significantly fewer obese pts reached CDAI LDA and DAS28-CRP LDA at wk 12; this difference was driven by those obese pts receiving low dosage of concomitant MTX (7.5 mg/wk), although by wk 24, the differences were no longer significant. There was low to no correlation between synovial vascularity/hypertrophy and clinical findings of swelling and tenderness. The proportion of pts with synovial vascularity=0 in the 3 BMI subgroups at wks 12 and 24 was not statistically different. Conclusions: Among obese RA pts initiating ADA, those on low dosage of concomitant MTX had poorer responses than pts in the normal and overweight categories, as measured clinically and by ultrasound imaging, although this effect was partly overcome by wk 24. Obese RA pts may have an improved clinical benefit if ADA is initiated with high (20 mg/week), rather than low dosage of concomitant MTX. References: Kaeley et al. ACR/ARHP 2013 Annual Meeting. Boston, MA, USA Acknowledgement: AbbVie: study sponsor, contributed to study design, data collection, analysis, interpretation and writing, reviewing and approval of abstract. Medical writing support: Naina Barretto of AbbVie Disclosure of Interest: G. Kaeley Consultant for: AbbVie, V. Ranganath Grant/research support from: Genentech, Pfizer, D. MacCarter Consultant for: AbbVie, Speakers bureau: AbbVie, A. Pangan Shareholder of: AbbVie, Employee of: AbbVie, X. Wang Shareholder of: AbbVie, Employee of: AbbVie, J. Kalabic Shareholder of: AbbVie, Employee of: AbbVie